Pengaruh Harga Dan Keragaman Menu Pada Keputusan Pembelian Konsumen Di The Arbanat Kitchen Café Lounge - Angga Kusuma Adi Mukti; Budi Wibowotomo; Laili Hidayati (Journal of Food Technology and Agroindustry dipublikasikan oleh Universitas Wiraraja, 2023)
One of the economic sectors that has been seriously affected by the corona virus is the culinary industry. Culinary business owners were forced to temporarily stop their business and some even had to face bankruptcy. The Arbanat Kitchen Café Lounge is one restaurant that is still surviving amid the threat of the coronavirus pandemic. The number of visits before the corona virus hit was 4,601 people, at the time the PSBB was implemented, visits fell by almost 100%. The survival of this restaurant cannot be separated from the variety of menus served and the innovations that continue to be presented, to support this, The Arbanat must adjust to the prices of basic ingredients that continue to soar without reducing the quality of taste. This study aims to determine the effect of menu diversity and price on purchasing decisions at The Arbanat Kitchen Café Lounge. This type of research is quantitative which uses data in the form of numbers which are analyzed statistically with SPSS. A total of 100 respondents were used as research samples. Data were analyzed by validity test, reliability test. Based on the results of descriptive analysis, showing the results of the price variable does not have a significant effect on consumer purchasing decisions while menu diversity has an influence on consumer purchasing decisions at The Arbanat Kitchen Café Lounge. Price variable and the diversity of the menu simultaneously has a significant effect on consumer purchasing decisions at The Arbanat Kitchen Café Lounge.